1980
DOI: 10.1029/jc085ic12p07488
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism for dry deposition of ozone to seawater surfaces

Abstract: A simple model, in which deposition is limited by diffusion through a thin laminar film of water, has successfully described the deposition of several gases to the sea. However, the deposition velocity of ozone to seawater is 10–30 times greater than this model predicts. This enhancement is attributed to significant reactions of ozone with halides and other components of seawater within the laminar surface layer, and a modified version of the model for ozone, and possibly other reactive gases, is proposed. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
147
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(159 citation statements)
references
References 14 publications
12
147
0
Order By: Relevance
“…However, the Arrhenius expression they reported (k = 1.44 × 10 22 exp(−73080/RT) M −1 s −1 ) contains a pre-exponential factor which is roughly 10 orders of magnitude greater than the diffusion limited reaction rate, and therefore appears to be unphysical. Hu et al (1995), using a similar droplet train technique with I − concentrations from 0.5-3 M and O 3 in the range 5 × 10 12 to 1 × 10 14 cm −3 , measured k(I − + O 3 ) = 4 × 10 9 M −1 s −1 at 277 K. Although they do not report a room temperature measurement, the room temperature value for k(I − + O 3 ) appears to be reasonably well established from a number of previous studies (Garland et al, 1980;Hoigné et al, 1985;Magi et al, 1997;Liu et al, 2001), lying in the range (1.2-2.4) × 10 9 M −1 s −1 . Thus the Hu et al (1995) result implies a slightly negative temperature dependence, although those authors state that within their experimental accuracy the reaction could have been temperature independent.…”
Section: Organicssupporting
confidence: 49%
“…However, the Arrhenius expression they reported (k = 1.44 × 10 22 exp(−73080/RT) M −1 s −1 ) contains a pre-exponential factor which is roughly 10 orders of magnitude greater than the diffusion limited reaction rate, and therefore appears to be unphysical. Hu et al (1995), using a similar droplet train technique with I − concentrations from 0.5-3 M and O 3 in the range 5 × 10 12 to 1 × 10 14 cm −3 , measured k(I − + O 3 ) = 4 × 10 9 M −1 s −1 at 277 K. Although they do not report a room temperature measurement, the room temperature value for k(I − + O 3 ) appears to be reasonably well established from a number of previous studies (Garland et al, 1980;Hoigné et al, 1985;Magi et al, 1997;Liu et al, 2001), lying in the range (1.2-2.4) × 10 9 M −1 s −1 . Thus the Hu et al (1995) result implies a slightly negative temperature dependence, although those authors state that within their experimental accuracy the reaction could have been temperature independent.…”
Section: Organicssupporting
confidence: 49%
“…These concentrations are usually very high in models due to a lack of deposition. This ozone deposition underestimation is rarely documented and quantified, but some previous studies showed that the dry deposition velocities used over oceans for gaseous species may be underestimated, due to a misrepresented turbulence as pointed out by Garland et al (1980), Ganzeveld et al (2009) the limitation due to the horizontal resolution, the model being not able to represent local ozone plumes as presented in Fig. 9.…”
Section: Ozone and Meteorological Vertical Profiles During The Atr Flmentioning
confidence: 93%
“…Iodine has recently been identified as a potential key element involved in climate change, as iodide reacts rapidly with O 3 , and is believed to be a major sink for atmospheric O 3 at the sea surface (Garland et al 1980). This reaction forms HOI and I 2 , and has also been suggested as a source of organic halogens (RI) (Martino et al 2009).…”
Section: Introductionmentioning
confidence: 99%